Study Literature Review: Mathematical Problem Solving Ability through Problem Based Learning Model assisted by Math City Map Application - Astiani Astiani (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Problem solving is a planned process that needs to be carried out in order to obtain a solution to a particular problem that requires systematic resolution steps. Systematic methods are used in the learning process to solve problems or face challenges needed in everyday life. The research method used is the Literature Review System with writing stages, namely data planning, screening, extraction, analysis. Search literature studies using google scholar data base using the Publish or Perish application. The use of the Math City Map approach can affect the problem-solving ability of students in mathematics learning. The use of the Math City Map approach helps learners understand and solve math problems better and effectively develop problem-solving skills. Learning outside the classroom using MCM applications provides a more immersive and challenging experience for students, helps them apply knowledge, and improves social and personal skills.